2
$\begingroup$

a) Compute the full Fourier series representation of $f(x) = e^{ax}, −π ≤ x < π.$

b) By using the result of a) or otherwise determine the full Fourier series expansion for the function $g(x)=\sinh(x), −π ≤ x < π.$

For part a) this is what I did and I'm pretty sure it's all correct. (Please let me know if it isn't!)

$$\begin{align} a_0\ &=\frac{1}{π}\int_{-π}^{π} f(x)\cos(0x)\;dx\\ &=\frac{1}{π}\int_{-π}^{π} e^{ax}\;dx=\frac{1}{π}\left[\frac{e^{ax}}{a}\right]^π_{-π}=\frac{e^{aπ}-e^{-aπ}}{aπ}\\ a_m\ &=\frac{1}{π}\int_{-π}^{π} e^{ax}\cos(mx)\;dx\\ &=\frac{1}{π}\left[\frac{e^{ax}\sin(mx)}{m}\right]^π_{-π}-\frac{1}{π}\int_{-π}^{π} \frac{ae^{ax}\sin(mx)}{m} dx\\ &=\frac{1}{π}\left[\frac{e^{ax}\sin(mx)}{m}\right]^π_{-π}+\frac{1}{π}\left[\frac{ae^{ax}\cos(mx)}{m^2}\right]^π_{-π}-\frac{1}{π}\int_{-π}^{π} \frac{a^2e^{ax}\cos(mx)}{m^2} dx\\ &=\frac{1}{π}\left[\frac{e^{ax}\sin(mx)}{m}+\frac{ae^{ax}\cos(mx)}{m^2}\right]^π_{-π}-\frac{a^2}{m^2}a_m\\ a_m\left(\frac{m^2+a^2}{m^2}\right)&=\frac{ae^{aπ}(-1)^m-e^{-aπ}(-1)^m}{πm^2}\\ a_m&=\frac{(-1)^m\left(ae^{aπ}-e^{-aπ}\right)}{π\left(m^2+a^2\right)} \end{align}$$

Then $$\begin{align} b_m&=\frac{1}{π}\int_{-π}^{π} e^{ax}sin(mx)\;dx\\ &=\frac{1}{π}\left[\frac{-e^{ax}\cos(mx)}{m}\right]^π_{-π}+\frac{1}{π}\int_{-π}^{π} \frac{ae^{ax}\cos(mx)}{m}\;dx\\ &=\frac{1}{π}\left[\frac{-e^{ax}\cos(mx)}{m}\right]^π_{-π}+\frac{1}{π}\left[\frac{ae^{ax}\sin(mx)}{m^2}\right]^π_{-π}-\frac{1}{π}\int_{-π}^{π} \frac{a^2e^{ax}\sin(mx)}{m^2}\;dx\\ &=\frac{1}{π}\left[\frac{-e^{ax}\cos(mx)}{m}+\frac{ae^{ax}\sin(mx)}{m^2}\right]^π_{-π}-\frac{a^2}{m^2}b_m\\ b_m\left(\frac{m^2+a^2}{m^2}\right)&=\frac{(-1)^{m+1}\left(e^{aπ}-e^{-aπ}\right)}{πm}\\ b_m&=\frac{m(-1)^{m+1}\left(e^{aπ}-e^{-aπ}\right)}{π\left(m^2+a^2\right)} \end{align}$$

so $$\begin{align} f(x)&=\frac{1}{2}a_0+\sum_{n=1}^{\infty}a_n\cos(nx)+b_n\sin(nx)\\ e^{ax}&=\frac{e^{aπ}-e^{-aπ}}{π}\left[\frac{1}{2a}+\sum_{n=1}^{\infty}\frac{(-1)^n}{n^2+a^2}(\cos(nx)-n\sin(nx))\right]\\ e^{ax}&=\frac{2}{π}\sinh(aπ)\left[\frac{1}{2a}+\sum_{n=1}^{\infty}\frac{(-1)^n}{n^2+a^2}(\cos(nx)-n\sin(nx))\right] \end{align}$$

but for part b) I wasn't sure of how to get the answer from part a) so instead I did this. I am also unsure if this is right. How do you do part b) using part a) ?

$$\begin{align} g(x)&=\sinh(x)\\ a_0\ &=\frac{1}{π}\int_{-π}^{π}\sinh(x)\cos(0x)\;dx\\ &=\frac{1}{π}\left[\cosh(x)\right]^π_{-π}=0\\ a_m\ &=\frac{1}{π}\int_{-π}^{π}\sinh(x)\cos(mx)\;dx\\ &=\frac{1}{π}\left[\frac{\sinh(x)\sin(mx)}{m}\right]^π_{-π}-\frac{1}{π}\int_{-π}^{π}\frac{\cosh(x)\sin(mx)}{m}\;dx\\ &=\frac{1}{π}\left[\frac{sinh(x)\sin(mx)}{m}\right]^π_{-π}+\frac{1}{π}\left[\frac{\cosh(x)\cos(mx)}{m^2}\right]^π_{-π}-\frac{1}{π}\int_{-π}^{π} \frac{\sinh(x)\cos(mx)}{m^2}\\ a_m\left(\frac{m^2+1}{m^2}\right)&=\frac{1}{π}\left[\frac{\sinh(x)sin(mx)}{m}+\frac{\cosh(x)\cos(mx)}{m^2}\right]^π_{-π}=0 \end{align}$$

Then $$\begin{align} b_m&=\frac{1}{π}\int_{-π}^{π}\sinh(x)\sin(mx)\;dx\\ b_m\left(\frac{m^2+a^2}{m^2}\right)&=\left[\frac{-\sinh(x)(-1)^{m}}{πm}\right]^π_{-π}\\ b_m&=\frac{-2m\sinh(π)(-1)^m}{π(m^2+1)} \end{align}$$

so $$\begin{align} g(x)&=\frac{1}{2}a_0+\sum_{n=1}^{\infty}a_n\cos(nx)+b_n\sin(nx)\\ \sinh(x)&=\frac{-2\sinh(π)}{π}\sum_{n=1}^{\infty}\frac{(-1)^nn\sin(nx)}{n^2+1} \end{align}$$

$\endgroup$
  • 6
    $\begingroup$ Congrats! You posted a lot of questions and never accepted an answer! $\endgroup$ – Jack D'Aurizio Sep 28 '16 at 15:46
8
$\begingroup$

We have: $$ \int_{-\pi}^{\pi}e^x \sin(nx)\,dx = \frac{2n}{1+n^2}(-1)^{n+1}\sinh \pi,$$ $$ \int_{-\pi}^{\pi}e^x \cos(nx)\,dx = \frac{2}{1+n^2}(-1)^{n}\sinh \pi,$$ hence:

$$ e^{x} = \frac{\sinh \pi}{\pi}+\frac{2\sinh \pi}{\pi}\sum_{n\geq 1}(-1)^n\frac{\cos(nx)-n\sin(nx)}{1+n^2}$$ and since $\sinh x$ is just the odd part of $e^x$ it follows that: $$ \sinh x = \frac{2\sinh \pi}{\pi}\sum_{n\geq 1}(-1)^{n+1}\frac{n\sin(nx)}{1+n^2}.$$ For $e^{ax}$ we have: $$ e^{ax} = \frac{\sinh(a\pi)}{a\pi}+\frac{2\sinh(a \pi)}{\pi}\sum_{n\geq 1}(-1)^n\frac{a\,\cos(nx)-n\sin(nx)}{a^2+n^2}.$$

$\endgroup$
  • $\begingroup$ For which values of $a$ does this work? $\endgroup$ – clathratus Jan 1 at 8:20
2
$\begingroup$

$\sinh x=\frac{e^x-e^{-x}}{2}$, so if you know the representations for $e^x$ and $e^{-x}$, you can find the one for $\sinh$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.